2016
DOI: 10.1534/g3.116.029462
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Interactions Between the Meiosis-Specific Cohesin Components, STAG3, REC8, and RAD21L

Abstract: Cohesin is an essential structural component of chromosomes that ensures accurate chromosome segregation during mitosis and meiosis. Previous studies have shown that there are cohesin complexes specific to meiosis, required to mediate homologous chromosome pairing, synapsis, recombination, and segregation. Meiosis-specific cohesin complexes consist of two structural maintenance of chromosomes proteins (SMC1α/SMC1β and SMC3), an α-kleisin protein (RAD21, RAD21L, or REC8), and a stromal antigen protein (STAG1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 61 publications
5
45
0
Order By: Relevance
“…The meiosis-specific SMC1β subunit is required for normal axis formation, chromosome loop size, and recombination in meiotic prophase I (Revenkova et al 2004; Novak et al 2008; Biswas et al 2013). The analysis of compound meiotic cohesin mutants confirms both that STAG3-containing cohesins are essential for normal axis formation, and that STAG3 has functional interactions with both the REC8 and RAD21L kleisins (Ward et al 2016). …”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…The meiosis-specific SMC1β subunit is required for normal axis formation, chromosome loop size, and recombination in meiotic prophase I (Revenkova et al 2004; Novak et al 2008; Biswas et al 2013). The analysis of compound meiotic cohesin mutants confirms both that STAG3-containing cohesins are essential for normal axis formation, and that STAG3 has functional interactions with both the REC8 and RAD21L kleisins (Ward et al 2016). …”
Section: Introductionmentioning
confidence: 73%
“…The Stag3 mouse mutant strain used in this study has previously been described (Hopkins et al 2014; Ward et al 2016). Briefly, the Stag3 allele was created by integration of the SB-cHS4core-SB-Tyro-WPRE-FUGW lentiposon transgene (LV2229) in intron 8 of Stag3 (http://www.mmrrc.org/catalog/sds.php?mmrrc_id=36275) in an FVB background.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that STAG2 was required for centromeric cohesion, whereas STAG3 was required to stabilise cohesin on chromosome axes and STAG1 had a specific role in telomere cohesion 9 28. Besides its canonical role in chromosome segregation, the cohesin complex indeed directly influences transcription via an essential role in transcriptional enhancer function 2.…”
Section: Discussionmentioning
confidence: 99%
“…In the complete STAG3 deficiency, the cells develop maximally to a testis tubular stage IV, but chromosomally they reflect leptotene cells as there are no axes (Winters et al, 2014). Very recently, double mutants of Stag3 with either Rec8 or Rad21L were described and show increased centromeric cohesion defects, very short AEs and, in case of the Stag3 -/- Rec8 -/- strain, are similar in phenotype to the Rec8 -/- Rad21L -/- spermatocytes [23]. …”
Section: Introductionmentioning
confidence: 99%